A rationale for reduced-frequency dosing of anidulafungin for antifungal prophylaxis in immunocompromised patients. (3rd December 2014) - Brüggemann, R. J. M.; Van Der Velden, W. J. F. M.; Knibbe, C. A. J.; Colbers, A.; Hol, S.; Burger, D. M.; Donnelly, J. P.; Blijlevens, N. M. A.
Abstract: Objectives: Reduced-frequency dosing strategies of anidulafungin may offer a more convenient way of providing adequate antifungal prophylaxis to patients at high risk of invasive fungal diseases. We aimed to provide the pharmacological rationale for the applicability of reduced-frequency dosing regimens. Methods: We defined two groups of 10 patients that were to receive anidulafungin at 200 mg every 48 h or 300 mg every 72 h. Blood samples were drawn daily and two pharmacokinetic curves were constructed after 1 and 2 weeks of treatment. A population pharmacokinetic model was developed using non-linear mixed-effects modelling. ClinicalTrials.gov identifier: NCT01249820. Results: The AUC over a 6 day period (IQR) for a typical patient on 200 mg every 48 h or 300 mg every 72 h resulted in 348 mg · h/L (310.6–386.7) and 359 mg · h/L (319.1–400.9), respectively, comparable to the licensed regimen [397.0 mg · h/L (352.4–440.5)]. In the final model, the volume of distribution proved to be dependent on the lean body mass and CL of cyclosporine A. All three regimens resulted in comparable dose-normalized exposure over time. Conclusions: We now have sufficient evidence to start using less frequent dosing regimens and demonstrate their value in clinical practice. These less frequently applied infusions enable more personalized care in an outpatient setting with reduced costs.